2018
DOI: 10.1080/17441692.2018.1444782
|View full text |Cite
|
Sign up to set email alerts
|

Types and sources of social support among adults living with type 2 diabetes in rural communities in the Dominican Republic

Abstract: Type 2 diabetes management hinges on various determinants, including the role of interpersonal relationships in self-management behaviours. The aim of this study was to explore the types and sources of social support received by adults in the diabetes diagnosis and self-management processes. We conducted qualitative interviews with 28 men and women at two rural clinics in the Dominican Republic and used a combination of narrative and thematic analytic techniques to identify key sources and types of social supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 31 publications
6
21
1
1
Order By: Relevance
“…Likewise, women from the Dominican Republic exhibit lower levels of perceived social support when compared to their counterparts and this may influence attendance to post-partum care for this subgroup. While this difference was found in our study, studies evaluating social support experiences in communities in Dominican Republic [ 29 ] and in Costa Rica [ 30 ], women consistently reported lower levels of social support compared to men.…”
Section: Discussioncontrasting
confidence: 96%
“…Likewise, women from the Dominican Republic exhibit lower levels of perceived social support when compared to their counterparts and this may influence attendance to post-partum care for this subgroup. While this difference was found in our study, studies evaluating social support experiences in communities in Dominican Republic [ 29 ] and in Costa Rica [ 30 ], women consistently reported lower levels of social support compared to men.…”
Section: Discussioncontrasting
confidence: 96%
“…Social and economic stressors were also salient among our participants as facets of living a normal life. 6 No le doy mente could be a local variation of mindfulness-based stress reduction (MBSR) by helping people with diabetes avoid dwelling on thoughts to protect their health. MBSR is an 8-week, groupbased intervention which promotes nonjudgmental acceptance of life events and emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research in which we identified gendered patterns in the experiences of diabetes, 6 we purposively sampled men and women. In June 2017, we recruited participants from one CCI/ILAC clinic when patients came for their routine care visits.…”
Section: Recruitment and Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The CCI program plans to bolster the lifestyle diabetes prevention efforts and emotional support [26] in the clinic populations and in the surrounding rural communities; this will be implemented primarily through augmenting the role of health promoters through training and support [12]. Community engagement for program sustainability and transformation of the dietary and physical activity environment is also a goal; patient associations have now been organized at each clinic [27] They are working on community gardens, raising poultry, and other fund-raising efforts to sustain the program.…”
Section: Future Directionsmentioning
confidence: 99%